Pretvorbeni faktorji za zunanjetrgovinske podatke o okroglem lesu za Slovenijo - Piškur, Mitja (Zbornik gozdarstva in lesarstva, 2009)
National roundwood trade data are important for international reporting and are an integral and important part of roundwood flow analysis. The main objective of the study was to calculate objective national conversion factors for transformation of mass into cubic metres solid volume under bark (net m3) and to propose uniform factors for main tree species. Official trade statistics data for the 2003-2006 period were used as raw data. Uniform proposed conversion factors for spruce and fir combined, beech and oak are 0.77 t/m3, 0.98 t/m3, and 1.12 t/m3, respectively. International conversion factors proposed by FAO are too low for Slovenia and consequently give higher official trade statistics data. The used method for calculation of national roundwood conversion factors for trade statistics is universal and repeatable. We propose periodical review of conversion factors.
Keywords: okrogli les; pretvorbeni faktorji; Slovenia; Slovenija; statistika; zunanja trgovina